2014
DOI: 10.1155/2014/461078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Juvenile Idiopathic Arthritis-Associated Uveitis

Abstract: Uveitis is a common complication of juvenile idiopathic arthritis (JIA) affecting up to 30% of patients with JIA. Although the typical bilateral chronic anterior uveitis associated with the persistent and extended oligoarticular and polyarticular, rheumatoid factor negative variants of JIA occurs predominantly in girls, boys may be more commonly affected in the HLA-B27 positive, enthesitis variant of JIA. While female gender has been associated with the development of the chronic anterior uveitis in children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
4
41
1
2
Order By: Relevance
“…A female predominance of about 60.4%∼84.2% in JIA-U has been reported in Western studies. Moreover, it has been suggested that increased frequency of JIA-U in girls is an outcome of the female predominance in young age of JIA onset (<6 years) [8][9][10][11]. However, males and females showed no difference in the incidence of uveitis in JIA in our study (male:female=1.0:1.2).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…A female predominance of about 60.4%∼84.2% in JIA-U has been reported in Western studies. Moreover, it has been suggested that increased frequency of JIA-U in girls is an outcome of the female predominance in young age of JIA onset (<6 years) [8][9][10][11]. However, males and females showed no difference in the incidence of uveitis in JIA in our study (male:female=1.0:1.2).…”
Section: Discussioncontrasting
confidence: 58%
“…Uveitis occurs most frequently in children with oligoarticular-type JIA, about 20%∼30% in Western data [3,8]. About 60.4%∼ 84.2% of JIA-U sufferers are female; however, ocular symptoms, signs, and complications are more severe in males in Western studies [8][9][10][11]. Most cases of uveitis develop around four years after JIA onset [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…The variation in these figures may partly be due to the referral cohorts from which the patients are selected, however, it should also be noted that uveitis can precede a diagnosis of arthritis in 3-7 % of children with JIA [10] and thus children presenting with uveitis need careful assessment for underlying systemic or infectious disease. When looking specifically at the prevalence of uveitis in those patients already known to have JIA, estimates of prevalence ranges from 11.6 % [11] to 30 % [12] although overall it appears to be decreasing over the past decade. Thus there is a well-established, reciprocal link between JIA and uveitis; uveitis is a frequent finding in JIA patients as well as JIA being a common underlying cause for the condition in children.…”
Section: Epidemiologymentioning
confidence: 99%
“…These include gender, JIA category, age of onset, and ANA and HLA-B27 positivity [3,10,12,14]. A younger age, female gender, oligoarticular disease and presence of ANA are risk factors for chronic anterior uveitis.…”
Section: Epidemiologymentioning
confidence: 99%
“…Данные о распространенности увеита, ассоции-рованного с ЮИА, весьма вариабельны: от 11,6 [5] до 30 % [66] всех детей с ЮИА, или у 30 % всех детей с ЮИА, имеющих антинуклеарные антитела [75].…”
Section: таблицаunclassified